Improved H2 utilization by Pd doping in cobalt catalysts for reductive amination of polypropylene glycol. Issue 73 (22nd December 2020) - Kim, Kyungjun; Kang, Dong Woo; Choi, Youngheon; Kim, Wanggyu; Lee, Hyunjoo; Lee, Jae W.
Abstract : Addition of Pd into Co helped remarkably to reduce cobalt oxide and nitride to cobalt metal by enhanced hydrogen dissociation and desorption. Abstract : Cobalt based catalysts having enhanced H2 dissociation and desorption were synthesized by inserting a trace amount of palladium. These catalysts were used for the reductive amination of polypropylene glycol (PPG) to polyetheramine (PEA). The catalytic activity toward PEA was significantly increased by incorporating an extremely low content of palladium (around 0.01 wt%) into cobalt based catalysts. The Pd inserted cobalt catalysts promoted reduction of cobalt oxide to cobalt metal and inhibited formation of cobalt nitride in the reductive amination. The Pd inserted cobalt catalysts not only enhanced hydrogen dissociation but also accelerated hydrogen desorption by increasing the electron density of cobalt through interaction between cobalt and palladium. These play a critical role in reducing cobalt oxide or cobalt nitride to cobalt metal as an active site for the reductive amination. Thus, the Pd inserted cobalt catalysts provide improved catalytic performance toward PEA production by maintaining the cobalt metal state.